Investigation of Lyophilized Microspheres Loaded with Leuprolide Acetate - Thanh Lam, Nguyen; Giao Thong, Ngo; Thi My Duyem, Tran; Thi Thuong, Bui; Thi Hai Yen, Tran (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 39 No 1, 2023)
Abstract: Leuprolide acetate (LA) - a nonapeptide, used for the treatment of some hormone-depending diseases, is unstable and very susceptible to degradation in the aqueous media. Poly (lactic-co-glycolic) acid (PLGA) is a copolymer of lactide and glycolide, that has generated tremendous interest in pharmaceutics because of their excellent biocompatibility, biodegradability, and mechanical strength. PLGA is used for the preparation of biocompatible biodegradable extended-release microspheres. However, the PLGA undergoes hydrolytic degradation in an aqueous environment through cleavage of its backbone ester linkages. As a consequence, PLGA-based microspheres loaded with LA are usually lyophilized to ensure the stability of LA and PGLA and reduce agglomeration, sedimentation, and size change of microspheres during storage. The aim of this present study is to evaluate the influence of lyoprotectants namely mannitol, trehalose, lactose, and saccharose on the stability of LA and characteristics of PLGA-based microspheres loaded with LA upon lyophilization. DSC and FTIR were used to evaluate the biocompatibility of LA and lyoprotectants. The results showed that there was no incompatibility between the LA and lyoprotectants. Mannitol solution 1.25% was used in freeze-drying PLGA-based microspheres loaded with LA. The obtained lyophilized microspheres had a good appearance and low moisture. Lyophilized microspheres after reconstitution had no significant change in drug content, size, and size distribution in comparison to that before freeze-drying. Keywords: Leuprolide acetate, PGLA, lyophilized, stability, biodegradable microspheres.